2021
DOI: 10.1530/raf-20-0041
|View full text |Cite
|
Sign up to set email alerts
|

Is pre-freeze sperm preparation more advantageous than post-freeze?

Abstract: Human sperm cryopreservation is characterised to this day by sub-optimal success rates. Interestingly, a traditional approach to improving post-thaw outcome has been to integrate standard sperm preparation techniques into freezing protocols as a means of selecting sperm with the highest fertilisation potential prior to insemination. However, no consensus has been reached yet regarding the optimal timing (before or after freezing) of this selection step. Following analysis of a total of 20 human semen samples, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 29 publications
1
7
0
Order By: Relevance
“…This phenomenon is contrary to the cryoprotective role of seminal plasma. Prefreezing strategies are aimed at optimizing sperm quality at baseline prior to cryopreservation and leading to an improved response of the sperm with regards to the osmotic and mechanical disruption associated with cryopreservation [26]. In this context, researchers have explored the preparation strategy to select normal sperm before cryopreservation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This phenomenon is contrary to the cryoprotective role of seminal plasma. Prefreezing strategies are aimed at optimizing sperm quality at baseline prior to cryopreservation and leading to an improved response of the sperm with regards to the osmotic and mechanical disruption associated with cryopreservation [26]. In this context, researchers have explored the preparation strategy to select normal sperm before cryopreservation.…”
Section: Discussionmentioning
confidence: 99%
“…In this context, researchers have explored the preparation strategy to select normal sperm before cryopreservation. A large number of studies have demonstrated favorable postthaw cellular viability based on the prefreeze approach [26][27][28][29][30], whereas others have shown comparable or contradictory outcomes [31][32][33]. Therefore, optimization of sperm cryopreservation strategy is complex and challenging that requires collaborative exploration in future, ideally through standardized experimental studies.…”
Section: Discussionmentioning
confidence: 99%
“…Young males during and after puberty are more likely able to ejaculate. Motile sperm of those samples can be frozen according to state-of-the-art protocols of the IVF or andrology/urology lab using slow freezing or vitrification before the gonadotoxic therapy starts ( 29 31 ). If the ejaculated sample does not contain enough sperm, the child can be counseled for testicular tissue cryopreservation ( 4 ).…”
Section: Options Of Fertility Preservation During and After Pubertymentioning
confidence: 99%
“…Notably, seminal plasma total antioxidant capacity is generally lower in men with impaired spermatogenesis ( Roychoudhury et al 2016 , Gholinezhad et al 2020 ) so the potential advantage of freezing unprepared samples may be smaller in this patient group. Conversely, several small studies have reported higher post-thaw total and progressively motility as well as vitality for semen samples prepared prior to freezing, suggesting that minimal post-thaw processing might be advantageous, particularly for donor sperm samples where count and motility are good ( Brugnon et al 2013 , Androni et al 2021 ).…”
Section: Introductionmentioning
confidence: 99%